Potent broadly neutralizing antibody VIR-3434 controls hepatitis B and D virus infection and reduces HBsAg in humanized mice - Lempp, Florian A.; Volz, Tassilo; Cameroni, Elisabetta; Benigni, Fabio; Zhou, Jiayi; Rosen, Laura E.; Noack, Julia; Zatta, Fabrizia; Kaiser, Hannah; Bianchi, Siro; Lombardo, Gloria; Jaconi, Stefano; et al. (Journal of hepatology, 2023)
Background & Aims - Chronic hepatitis B is a global public health problem, and coinfection with hepatitis delta virus (HDV) worsens disease outcome. Here, we describe a hepatitis B virus (HBV) surface antigen (HBsAg)-targeting monoclonal antibody (mAb) with the potential to treat chronic hepatitis B and chronic hepatitis D. - Methods - HBsAg-specific mAbs were isolated from memory B cells of HBV vaccinated individuals. In vitro neutralization was determined against HBV and HDV enveloped with HBsAg representing eight HBV genotypes. Human liver-chimeric mice were treated twice weekly with a candidate mAb starting three weeks post HBV inoculation (spreading phase) or during stable HBV or HBV/HDV coinfection (chronic phase). - Results - From a panel of human anti-HBs mAbs, VIR-3434 was selected and engineered for pre-clinical development. VIR-3434 targets a conserved, conformational epitope within the antigenic loop of HBsAg and neutralized HBV and HDV infection with higher potency than Hepatitis B Immunoglobulins in vitro. Neutralization was pan-genotypic against strains representative of HBV genotypes A-H. In the spreading phase of HBV infection in human liver-chimeric mice, a parental mAb of VIR-3434 (HBC34) prevented HBV dissemination and intrahepatic HBV RNA and cccDNA increase. In the chronic phase of HBV infection or co-infection with HDV, HBC34 treatment decreased circulating HBsAg by >1 log and HDV RNA by >2 logs. - Conclusions - The potently neutralizing anti-HBs mAb VIR-3434 reduces circulating HBsAg and HBV/HDV viremia in human liver-chimeric mice. VIR-3434 is currently in clinical development for treatment of patients with chronic hepatitis B or D. - Impact and implications - Chronic infection with hepatitis B virus and co-infection with hepatitis D virus place approximately 290 million individuals worldwide at risk for severe liver disease and cancer. Available treatments result in low rates of functional cure or require lifelong therapy that does not eliminate the risk of liver disease. We isolated and characterized a potent, human antibody that neutralizes hepatitis B and D viruses and reduces infection in a mouse model. This antibody could provide a new treatment for patients with chronic hepatitis B and D.
Gesehen am 09.08.2023